2010
DOI: 10.1001/archsurg.2010.177
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Performance on the American Board of Surgery Qualifying and Certifying Examinations

Abstract: Residents who are more likely to fail the ABS qualifying and certifying examinations can be identified by a low USMLE Step 1 score and by poor performance on the ABSITE at any time during residency. These findings support the use of the USMLE Step 1 score in the surgical residency selection process and a formal academic intervention for residents who perform poorly on the ABSITE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 8 publications
7
108
0
1
Order By: Relevance
“…Factors such as sex, age at the time of training, and international medical school training have had varied effects on examination performance. [8][9][10][11][12][13] Graduates from larger training programs tended to have better Results controlled for in-training examination score and yearspecific anomalies using a standard fixed-effects model. *Results for first-time test takers certification performance in pediatrics, ophthalmology, and general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as sex, age at the time of training, and international medical school training have had varied effects on examination performance. [8][9][10][11][12][13] Graduates from larger training programs tended to have better Results controlled for in-training examination score and yearspecific anomalies using a standard fixed-effects model. *Results for first-time test takers certification performance in pediatrics, ophthalmology, and general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10][11][12][13][14][15][17][18][19][20][21][22][23][24][25] The results from our study also indicate that predictors such as those ITEs that test knowledge gained over the first two years of anesthesiology training can be used as predictors of passing the ABA Part 1 examination. However, we did not find either the PGY-0 ITE (administered at the beginning of the intern year) or the CB ITE (administered at the beginning of the CA-1/first anesthesiology residency year) to be particularly good predictors of passing the ABA Part 1 examination.…”
Section: Table 2 Stepwise Regression Analyses Predictors From Ites Bmentioning
confidence: 85%
“…28 Studies in other specialties have also demonstrated that USMLE scores were positive predictors of specialty board certification. 4,[6][7][8][9][10][11][12][13][14][15][16][17] In 1986, Warrick and Crumrine 32 actually found a negative correlation between the National Board of Medical Examiners (NBME) Part 1 examination, which the USMLE Step 1 examination has replaced, and the ABA-ASA ITE. In that study, higher scores on the NBME Part 1 examination were associated with lower ABA-ASA ITE scores.…”
Section: Table 2 Stepwise Regression Analyses Predictors From Ites Bmentioning
confidence: 99%
See 2 more Smart Citations